PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL: PERBANDINGAN HUKUM PIDANA POSITIF DAN PIDANA ISLAM - Saepul Rochman; Haerul Akmal; Yaffi Jananta Andriansyah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2021)
This article aims to compare the application of criminal defamation norms through social media. The method used in this study is a normative method with comparative law approach. The results of this study indicate that the criminal act of defamation is sentenced to one year in prison. Whereas in Islamic criminal law as a source of positive law, according to the school of jurisprudence (madzhab) other than Syafi'iyah, the punishment is exile (ta'zir) according to the decision of the caliph or sultan or qadhi. Only the Shafi'iyah school determines through a legal analogy (qiyas). That the defendant is sentenced to one year's seclusion